Acoustic characteristics of the advertisement and territorial calls of Phyllodytes tuberculosus Bokermann, 1966 (Amphibia: Anura: Hylidae) - Juncá, Flora Acuña; Napoli, Marcelo Felgueiras; Cedraz, Juliana; Nunes, Ivan (Zootaxa, 2012)
The treefrog genus Phyllodytes Wagler includes 11 species distributed throughout eastern Brazil (Frost 2011), mostly in the Atlantic Forest biome. Hylids of the genus Phyllodytes are bromeligen (sensu Peixoto 1995) and vocalizations of only four species have been described until now (Lima et al. 2008). Here we describe for the first time the acoustic characteristics of the advertisement and territorial calls of P. tuberculosus Bokermann (Fig. 1A) from its type locality.